Polylactic acid graft copolymers, their preparation method and use

The method enhances PLA by ring-opening polymerization and high-temperature chain extension, achieving a high graft rate and molecular weight, addressing the limitations of conventional PLA modification methods.

JP2025502485AActive Publication Date: 2025-01-24CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024543504
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-29
Filing Date
2023-01-04
Publication Date
2025-01-24
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

Conventional methods for modifying poly lactic acid (PLA) result in low molecular weight, low graft ratio, and inferior mechanical characteristics and heat resistance, making it unsuitable for industrial applications.

Method used

A method involving ring-opening polymerization followed by grafting with maleic anhydride, then high-temperature chain extension, to produce a polylactic acid graft copolymer with enhanced molecular weight and graft group content.

Benefits of technology

The method achieves a graft rate of up to 50% and a molecular weight of 1×10^5 to 4×10^5, improving mechanical strength and heat resistance while maintaining environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502485000001_ABST
    Figure 2025502485000001_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer synthesis, and specifically relates to a polylactic acid graft copolymer, its preparation method, and use. The polylactic acid graft copolymer contains a repeating structural unit of the structure represented by formula (A), and is characterized in that it has a right-angle tear strength of 120 kN / m or more, preferably 135-150 kN / m, and a breaking elongation of 30% or more, preferably 35-45%. The polylactic acid graft copolymer prepared by the method described in the technical proposal of the present invention significantly improves the grafting efficiency, and improves the toughness, breaking elongation, and glass transition temperature of the polylactic acid material, and the prepared graft-modified polylactic acid copolymer material is environmentally friendly and completely biodegradable. [Formula 1] JPEG2025502485000015.jpg29169 (R 1 is H or a graft group, and the R 1 At least a portion of the groups is a graft group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of Chinese patent application No. 202210110898.2, filed on January 29, 2022, the contents of which are incorporated herein by reference.

[0002] [Technical field] The present invention relates to the technical field of polymer synthesis, in particular to polylactic acid graft copolymers, their preparation methods and uses. [Background technology]

[0003] In recent years, research into bio-based composite materials has attracted attention in academia and industrial production, with the aim of reducing the harm to the natural environment caused by fossil energy. Polylactic acid (PLA) is a thermoplastic resin with superior strength and processability compared to polyolefins and polyethylene terephthalate, which are commonly used in industrial products. PLA is produced by polymerization of lactic acid monomer, which is produced by fermentation of plants such as corn, potato, cotton, and hemp. The raw material for lactic acid is renewable, and PLA obtained by polymerizing renewable lactic acid also has characteristics such as high strength, good processability, and excellent mechanical properties. However, PLA also has several disadvantages, such as high brittleness, high hydrophobicity, low impact strength, high cost, and poor stability at high temperatures and certain humidity. Due to these disadvantages, PLA is difficult to use directly in industrial products like general plastics such as polyethylene and polypropylene, and requires modification processing. Currently, many modification processing methods are used to optimize the performance of polylactic acid by blending it with other plastics, but this method, although simple, does not fundamentally change the properties of polylactic acid materials. Furthermore, attempts have been made to modify the polylactic acid material itself by other methods such as graft modification. Maleic anhydride is a polar monomer material and a high-performance graft modifier with a five-membered ring structure. When graft-modifying polylactic acid, it can improve the polarity of the polylactic acid material, and because maleic anhydride has a cyclic structure, it can also modify the toughness of the polymer chain of polylactic acid.

[0004] At present, the commonly used methods at home and abroad to use maleic anhydride to modify the properties of other materials are as follows: first, polyethylene, polystyrene, starch, lignin, etc. are grafted with maleic anhydride to obtain pre-grafted materials, and then the pre-grafted materials are blended and added to polylactic acid materials to improve the toughness of polylactic acid, but the effect of this modification method is not clear. Some researchers directly graft maleic anhydride onto the polymer chains of polylactic acid by reactive extrusion, thereby changing the non-polar structure of polylactic acid.

[0005] CN108192033A discloses a method for preparing L-lactide / glycolide / ε-caprolactone terpolymer directly grafted with maleic anhydride, which involves polymerizing L-lactide, glycolide, and α-caprolactone in a certain ratio under the action of a catalyst to obtain crude PLLGC, dissolving the crude PLLGC in chloroform, reprecipitating with methanol, and filtering the white solid to obtain purified PLLGC. Maleic anhydride is added to the purified PLLGC and reacted in the solution, so that maleic anhydride is grafted onto the PLLGC copolymer. Although the synthesized polylactic acid is of high purity, the grafting rate of maleic anhydride is less than 1%, and the reaction adopts solution polymerization, which has many disadvantages, such as the organic solvent used is highly toxic, the molecular weight of the synthesized polymer is low, and it is disadvantageous for industrialization.

[0006] CN103570884A discloses a method for preparing maleic anhydride modified poly(lactide-co-glycolide), which is prepared by adding L / D-lactide, glycolide and maleic anhydride in a certain ratio to an ampoule, and polymerizing the mixture at 130-170°C for 12-60 hours under the action of stannous octanoate catalyst to prepare crude poly(lactide-co-glycolide) (MPLGA), dissolving MPLGA in chloroform, reprecipitating with methanol, and filtering the white solid to obtain purified MPLGA. Although the polymer prepared by this method has a narrow molecular weight distribution, it also undergoes a grafting reaction of maleic anhydride during the polymerization process, which causes many problems such as low grafting rate of the product, long polymerization reaction time, and low molecular weight of the polymer, which are unfavorable for industrial production.

[0007] As described above, maleic anhydride-grafted polylactic acid produced by the prior art generally has a low molecular weight, a low maleic anhydride graft ratio, and poor mechanical properties and heat resistance. Summary of the Invention [Problem to be solved by the invention]

[0008] The object of the present invention is to provide a polylactic acid graft copolymer in which both the molecular weight and the content of graft groups are significantly improved, so that the polylactic acid graft copolymer material has good mechanical properties, heat resistance, and degradability, and is easy to produce industrially. [Means for solving the problem]

[0009] In order to achieve the above object, the first aspect of the present invention is a polymerizable composition comprising a repeating structural unit having a structure represented by formula (A): The present invention provides a polylactic acid graft copolymer characterized in that the right-angle tear strength is 120 kN / m or more, preferably 135 to 150 kN / m, and the breaking elongation is 30% or more, preferably 35 to 45%. [ka] (where R 1 is H or a graft group, and the R 1 At least a portion of the groups is a graft group.

[0010] A second aspect of the present invention is (1) contacting lactide with a grafting monomer under nucleophilic addition reaction conditions to obtain a nucleophilic addition product; Step (2) of mixing the nucleophilic addition product obtained in step (1) with a catalyst and an initiator under ring-opening polymerization reaction conditions to perform low-temperature prepolymerization to obtain a ring-opening polymerization product; and step (3) polymerizing the ring-opening polymerization product obtained in step (2) at high temperature in the presence of an antioxidant under chain extension reaction conditions.

[0011] A third aspect of the present invention provides a polylactic acid graft copolymer prepared by the above method.

[0012] A fourth aspect of the present invention provides the use of the polylactic acid graft copolymer according to the first or third aspect in the preparation of agricultural mulch films, food packaging materials, and medical and sanitary products. Effect of the Invention

[0013] Compared with the prior art, the present invention provides a new route for synthesizing polylactic acid graft copolymers, which is to first use graft monomers to graft lactide under nucleophilic addition reaction conditions to obtain nucleophilic addition products rich in graft groups, then prepolymerize the nucleophilic products rich in graft groups under ring-opening polymerization reaction conditions at low temperatures to obtain ring-opening polymerization products, and finally polymerize the ring-opening polymerization products at high temperatures under chain extension reaction conditions to obtain maleic anhydride graft polylactic acid copolymers with high molecular weights. Compared with the prior art of ring-opening copolymerization followed by grafting, the present invention of grafting followed by ring-opening copolymerization can effectively increase the content of graft groups (i.e., graft ratio), and the subsequent high-temperature polymerization can effectively increase the molecular weight of the polymer.

[0014] By using the method for preparing polylactic acid graft copolymer according to the present invention, it is theoretically possible to obtain a polylactic acid graft copolymer with a graft ratio of 50% or even 100%. By adjusting the ratio of raw materials, the content of graft groups in the polylactic acid graft copolymer can be effectively adjusted, and thus the properties of the polylactic acid graft copolymer can be adjusted.

[0015] The polylactic acid graft copolymer according to the present invention has high flexibility despite its relatively high molecular weight. The prepared graft-modified polylactic acid copolymer material has excellent perpendicular tear strength and breaking elongation, is environmentally friendly and completely biodegradable. Since the terminal hydroxyl of the polylactic acid graft copolymer is retained, the polylactic acid graft copolymer can be further modified via this functional group to further adjust the properties of the polylactic acid graft copolymer. [Brief description of the drawings]

[0016] [Figure 1] 1 shows infrared absorption spectra of each substance in Example 1: (a) L-lactide (LA), (b) maleic anhydride (MAH), and (c) maleic anhydride-grafted lactide. [Diagram 2] FIG. 1 shows infrared absorption spectra of each substance in Example 1, including (a) polylactic acid (PLA), (b) maleic anhydride (MAH), (c) maleic anhydride-grafted polylactic acid, and (d) the infrared difference spectrum after subtracting the spectrum of maleic anhydride-grafted polylactic acid and polylactic acid. [Diagram 3] 13C NMR spectra of each substance in Example 1: (a) L-lactide, (b) maleic anhydride-grafted lactide. [Figure 4] 13C NMR spectra of each substance in Example 1: (a) polylactic acid (PLA) and (b) maleic anhydride-grafted polylactic acid. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The range endpoints and any values ​​disclosed herein are not intended to be limiting to the exact ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. In the case of numerical ranges, the individual range endpoints, the individual range endpoints and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.

[0018] In order to achieve the above object, the first aspect of the present invention is a polymerizable composition comprising a repeating structural unit having a structure represented by formula (A):

[0019] The present invention provides a polylactic acid graft copolymer characterized by a right-angle tear strength of 120 kN / m or more, preferably 135-150 kN / m, and a breaking elongation of 30% or more, preferably 35 to 45%. [ka] (where R 1 is H or a graft group, and the R 1 At least a portion of the groups is a graft group.

[0020] The polylactic acid graft copolymer may be represented by the following general formula: [ka] (Here, R1 ’’ , R2 ’’ , … and R n ’’ are each independently selected from H, a graft group represented by formula (I), and a graft group represented by formula (II).

[0021] According to the present invention, the content of the graft group is 1 The total amount of these is 10 mol % or more, preferably 30 mol % or more, and more preferably 40 mol % or more.

[0022] According to the present invention, the graft group may be any of various groups that can be grafted to lactide / polylactic acid and can make the right-angle tear strength of the polylactic acid material 120 kN / m or more, preferably 135 to 150 kN / m, and the breaking elongation 30% or more, preferably 35 to 45%, and preferably the graft group has a structure represented by formula (I) and / or formula (II). [ka] (wherein R1, R2, R3, R4, and R5 are each independently hydrogen or a C1-C4 substituted or unsubstituted alkyl, and R6 is a C1-C6 substituted or unsubstituted alkyl or a C6-C20 aryl.)

[0023] In the present invention, the C1-C6 substituted or unsubstituted alkyl may be any of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, n-hexyl, and isohexyl, and the alkyl may be substituted with one or more of halogen, nitro, primary amino, secondary amino, and tertiary amino. The halogen may be one or more of fluorine, chlorine, bromine, and iodine.

[0024] The C6 to C20 aryl may be any one of phenyl, methylphenyl, ethylphenyl, dimethylphenyl, diphenyl, biphenyl, and polyphenyl.

[0025] According to the present invention, taking the example of a graft copolymer having maleic anhydride as a graft group, the polylactic acid graft copolymer 13 In CNMR, the peak of the carbon atom of the anhydride group at the chemical shift position of about 169 ppm and the peak of the carbon atom after the carbon-carbon double bond of maleic anhydride is broken at the chemical shift position of about 72 ppm are characteristic of the mid-chain grafting method of the present invention. In the present invention, "near" refers to an error within the acceptable range in the art caused by possible factors such as test equipment and personal operation, and is generally ±5 ppm. Therefore, the present invention calls the method of ring-opening polymerization followed by grafting as chain end grafting.

[0026] According to the present invention, the weight average molecular weight of the polylactic acid graft copolymer is 1×10 5 -4×10 5 The polylactic acid graft copolymer according to the present invention has high flexibility while having a relatively high molecular weight. In the prior art, the polylactic acid grafted to the chain end usually has a molecular weight of 3×10 5 The perpendicular tear strength is less than 100 kN / m, typically 80 to 95 kN / m, and the breaking elongation is 10% or less, typically 5 to 10%.

[0027] According to the present invention, the glass transition temperature of the polylactic acid graft copolymer is 80 to 100° C. The glass transition temperature of the polylactic acid graft copolymer according to the present invention is higher than the glass transition temperature of polylactic acid grafted to the chain end in the prior art, which is advantageous in improving the heat resistance of the material.

[0028] According to the present invention, at least one end group of the polylactic acid graft copolymer contains a hydroxyl group, and therefore the polylactic acid graft copolymer can be further modified through this functional group. The presence of the terminal hydroxyl group can be measured by chemical titration.

[0029] In the present invention, the perpendicular tear strength and breaking elongation are measured by a universal mechanical testing machine, the weight average molecular weight is measured by a gel chromatography method, the glass transition temperature is measured by a differential scanning calorimeter method, and the graft ratio is measured by a chemical titration method. The details are explained below.

[0030] In a second aspect of the invention, the method comprises the steps of: (1) contacting lactide with a grafting monomer under nucleophilic addition reaction conditions to obtain a nucleophilic addition product; Step (2) of mixing the nucleophilic addition product obtained in step (1) with a catalyst and an initiator under ring-opening polymerization reaction conditions to perform low-temperature prepolymerization to obtain a ring-opening polymerization product; and step (3) of polymerizing the ring-opening polymerization product obtained in step (2) at high temperature in the presence of an antioxidant under chain extension reaction conditions to increase the molecular weight of the polylactic acid graft copolymer.

[0031] The present invention adopts a method of grafting followed by ring-opening polymerization, which can effectively ensure the grafting rate, and can ensure that a polylactic acid graft copolymer with a higher molecular weight can be obtained through high-temperature polymerization, so that the resulting polymer has high flexibility and heat resistance.

[0032] Preferably, the grafting monomer is a monomer of formula (i) and / or formula (ii). [ka] (Here, R1', R2', R3', R4', R5', and R6' correspond to and are similar to R1, R2, R3, R4, R5, and R6 defined above, respectively, and will not be described in detail here.)

[0033] According to the present invention, in step (1), in order to realize a grafting reaction between lactide and a graft monomer such as maleic anhydride, maleic anhydride is grafted onto lactide through double bond cleavage through a nucleophilic addition reaction to obtain a graft product, in which the nucleophilic addition reaction is carried out in the presence of an initiator.

[0034] In the present invention, the lactide is at least one selected from L-lactide, D-lactide, and meso-lactide, and preferably L-lactide and / or D-lactide.

[0035] According to the present invention, the initiator is a peroxide initiator, preferably dicumyl peroxide and / or 2,5-dimethyl-2,5-bis-(t-butylperoxy)hexane.

[0036] According to the present invention, the amount of the initiator added is 0.1 to 5 wt %, preferably 0.5 to 2 wt %, of the amount of the lactide used.

[0037] According to the present invention, step (1) is a constant temperature reaction under an inert gas flow, preferably a nitrogen gas flow, and a vacuum condition, and the conditions of the nucleophilic addition reaction include a reaction temperature of 50-150°C, preferably 80-120°C, a reaction pressure of 2-100 kPa, preferably 20-60 kPa, a reaction time of 0.5-10 h, preferably 2-6 h, and an air flow velocity of the nitrogen flow protection of 0.5-6 m / s, preferably 2-4 m / s.

[0038] In the present invention, unless otherwise specified, all pressures referred to above refer to absolute pressures.

[0039] According to the present invention, in step (1), the lactide has an optical purity of 99.0 to 99.6%, preferably 99.4 to 99.6%, and may be a homemade product or a commercially available product.

[0040] According to the present invention, in order to obtain better toughness, the graft ratio of the graft group (i.e., the content of the graft group in the polylactic acid material) is improved, and preferably, the amount of the graft monomer added is 100 to 300 wt %, preferably 150 to 200 wt %, of the amount of the lactide used.

[0041] Taking maleic anhydride and L-lactide as an example, the main reactions occurring in step (1) are shown in the following formulas (a) and (b). [ka]

[0042] Theoretically, the grafting rate of the product obtained by formula (a) is 100%, and the grafting rate of the product obtained by formula (b) is 50%.

[0043] According to the present invention, the method further comprises the step of removing the lactide not involved in the nucleophilic addition reaction by vacuum distillation after the step (1), and subjecting the obtained product to the reaction in step (2).

[0044] According to the present invention, the conditions of the reduced pressure distillation include a temperature of 100 to 200°C, preferably 120 to 150°C, a pressure of 0 to 100 kPa, preferably 10 to 50 kPa, and a time of 1 to 10 hours, preferably 2 to 6 hours.

[0045] According to the present invention, in the step (2), the catalyst catalyzes the ring-opening reaction of lactide having a graft group grafted thereto, and is preferably at least one of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum, and stannous chloride, more preferably stannous octoate.

[0046] According to the present invention, the amount of the catalyst added may be 0.1-5 wt %, preferably 0.5-3 wt %, of the total weight of the nucleophilic addition product.

[0047] According to the present invention, the initiator in step (2) adopts an alkyl hydroxy or aromatic hydroxy initiator, which initiates the polymerization reaction after the ring-opening reaction of the lactide having the grafted group introduced therein, and the initiator is preferably at least one selected from glycerol, xylitol, ethylene glycol, and triphenylphosphine, and preferably triphenylphosphine.

[0048] According to the present invention, the amount of the initiator added may be 0.05 to 5 wt %, preferably 0.3 to 2 wt %, of the total weight of the nucleophilic addition product.

[0049] According to the present invention, step (2) is a low-temperature polymerization under an inert gas flow, preferably a nitrogen flow, and negative pressure conditions, and the conditions of the ring-opening polymerization reaction in step (2) include a reaction temperature of 100-150°C, preferably 120-140°C, a reaction pressure of 100-1000kPa, preferably 200-500kPa, a reaction time of 2-15h, preferably 3-8h, and a gas velocity of the nitrogen flow of 0.5-6m / s, preferably 2-4m / s.

[0050] According to the present invention, the antioxidant in step (3) is to prevent the oxidation of the polylactic acid oligomer in step (2) and ensure further polymerization and chain extension reaction at higher temperatures. The antioxidant can be various substances that can prevent the oxidation of polylactic acid at high temperatures and do not have adverse effects on the polylactic acid material, such as at least one selected from phosphite-based antioxidants, alkyl polyphenol-based antioxidants, and thiobisphenol-based antioxidants, and is preferably triphenyl phosphite.

[0051] According to the present invention, the amount of the antioxidant added is 0.1 to 5 wt %, preferably 0.5 to 2 wt %, of the total weight of the ring-opening polymerization product.

[0052] According to the present invention, in the step (3), the temperature of the chain extension reaction is 140 to 250°C, preferably 160 to 200°C.

[0053] According to the present invention, the step (3) is preferably carried out in a twin-screw extruder. The reaction process is carried out by adding the ring-opening polymerization product and the antioxidant to the twin-screw extruder, performing high-temperature reactive kneading, extruding and granulating, and finally obtaining the polylactic acid graft copolymer.

[0054] The conditions for the high temperature polymerization include an inlet temperature of the twin-screw extruder of 140 to 160° C. and an outlet temperature of 170 to 190° C. The residence time of the material in the twin-screw extruder is preferably 13 to 23 minutes.

[0055] The method for preparing the polylactic acid graft copolymer according to the present invention is a method in which a bulk prepolymerization reaction of lactide is carried out in a reactor and copolymerized in combination with a twin-screw extruder, and the reaction operation is simple and industrial production is easy.

[0056] Taking maleic anhydride and L-lactide as an example, the main reaction processes in steps (2) and (3) are shown in the following formulas (c) and (d): [ka]

[0057] In the above formula (c) and formula (d), x and y represent the degree of polymerization of MA-LLA, where y is greater than x, and z represents the number of moles.

[0058] A third aspect of the present invention provides a polylactic acid graft copolymer prepared by the above method.

[0059] The polylactic acid graft copolymer prepared by the above method has a right-angle tear strength of 120 to 150 KN / m, a breaking elongation of 30 to 45%, a glass transition temperature of 80 to 100°C, and a molecular weight of 1×10 5 ~4×10 5 , the graft rate is 40-50%.

[0060] A fourth aspect of the present invention provides the use of the polylactic acid graft copolymer according to the first or third aspect in the preparation of agricultural mulch films, food packaging materials, and medical and sanitary products.

[0061] The polylactic acid graft copolymer has a high graft ratio, and therefore can improve flexibility and heat resistance while ensuring a higher molecular weight, and can be suitably used for the preparation of agricultural mulch films, food packaging materials, and medical and sanitary products.

[0062] The present invention will now be described in more detail with reference to examples. In the following examples, all reagents used are commercially available unless otherwise specified.

[0063] The following is a characteristic parameter test method according to the present invention.

[0064] (1) Graft ratio of graft groups The graft ratio of the graft group of the polylactic acid graft copolymer was measured by chemical titration. Specifically, a certain mass of the polylactic acid graft copolymer was weighed into an Erlenmeyer flask, dissolved by adding a certain amount of tetrahydrofuran, and a small amount of thymol blue / DMF indicator was added dropwise. The mixture was titrated with an excess of 0.05 mol / L potassium hydroxide in ethanol, and then back-titrated with 0.01 mol / L HCl-isopropyl alcohol solution. Graft ratio = n2 / n1 × 100%, n1 = (m0-m2) / M1, n2 = m2 / M2, i.e., graft ratio = [(0.05V KOH -0.01V HCl )×2×M1] / [m0-(0.05V KOH -0.01V HCl ) × 2 × M2], where m0 is the weighted mass of the polylactic acid graft copolymer (unit: g), m2 is the total mass of the grafted groups on the polylactic acid molecular chain calculated based on the consumed KOH, n1 is the degree of polymerization of polylactic acid, i.e., the amount of lactic acid units, n2 is the amount of grafted groups on the polylactic acid molecular chain, M1 is the molar mass of lactic acid, M2 is the molar mass of the grafted groups, V KOH is the volume of potassium hydroxide ethanol solution added (unit: mL), V HCl is the volume of the HCl-isopropyl alcohol solution consumed by the titration (unit: mL).

[0065] (2) Right-angle tear strength and breaking elongation: Measured using a universal mechanical testing machine according to GB / T 1039-1992 standard.

[0066] (3) Detection of terminal hydroxyl: Use phthalic anhydride method and measure according to GB / T 12008.3-2009 standard.

[0067] (4) Glass transition temperature: Measured using a differential scanning calorimeter (DSC) (DSC 204, manufactured by Netzsch-Feinmahltechnik GmbH). The test conditions are as follows: The sample amount is 5-10 mg, and the sample is first heated from room temperature to 200°C at a heating rate of 10°C / min, and kept at that temperature for 5 min to remove the thermal history of the sample. After that, the sample is rapidly cooled to -20°C, and the temperature is increased from -20°C to 200°C at a heating rate of 10°C / min. Nitrogen is introduced as a protective gas throughout the entire test process. The nitrogen flow rate is set to 50 mL / min.

[0068] (5) Weight average molecular weight of polymer: Measured by gel permeation chromatography (GPC). Gel permeation chromatography (GPC Waters 1515 system) is used to characterize the molecular weight of polylactic acid graft copolymer sample. Chromatographically pure THF is the mobile phase, the flow rate is 1.0 ml / min, and the column temperature is 35°C. Before the test, the sample is dissolved in THF at a concentration of 5 mg / mL, filtered through a polytetrafluoroethylene (PTFE) filter membrane with a pore size of 0.22 μm, and then calibrated with narrow-distribution polystyrene (PS) standards. Example 1

[0069] (1) L-lactide and maleic anhydride were added to a reaction vessel, dicumyl peroxide was added as an initiator, and the mixture was heated under nitrogen flow and vacuum to carry out a nucleophilic addition reaction. The reaction temperature of the nucleophilic addition reaction was 105°C, the reaction pressure was 45kPa, the reaction time was 3.5h, the nitrogen flow rate was 2m / s, the amount of maleic anhydride added was 155wt% of the amount of L-lactide used, and the amount of dicumyl peroxide added was 0.7wt% of the amount of L-lactide used. (2) In step (1), L-lactide not involved in the nucleophilic addition reaction was removed by vacuum distillation to obtain a purified nucleophilic addition product. The vacuum distillation was carried out at a temperature of 130°C, a pressure of 25 kPa, and a time of 3.5 h. Chromatographic detection revealed that the purified product was maleic anhydride grafted L-lactide (MA-LLA). (3) The maleic anhydride grafted L-lactide (MA-LLA) obtained in step (2) was subjected to ring-opening polymerization reaction in a nitrogen flow atmosphere by the action of a catalyst and an initiator, and low-temperature prepolymerization was performed to obtain MA-LLA oligomer as a ring-opening polymerization product. The ring-opening polymerization reaction was carried out at a reaction temperature of 140°C, a reaction time of 4.5 h, a reaction pressure of 350 kPa, and a nitrogen flow rate of 3.5 m / s. The amount of stannous octanoate added as a catalyst was 0.75 wt% of the amount of MA-LLA used, and the amount of triphenylphosphine added as an initiator was 0.35 wt% of the amount of MA-LLA used. The weight-average molecular weight of the MA-LLA oligomer was 5,500. (4) The MA-LLA oligomer obtained in step (3) was added to a twin-screw extruder together with an antioxidant, subjected to high-temperature reactive kneading, subjected to a chain extension reaction of the MA-LLA oligomer, extruded and granulated, and finally obtained a maleic anhydride grafted polylactic acid copolymer material (MA-PLLA), which is a polylactic acid graft copolymer. Based on the weight of the MA-LLA oligomer, the amount of triphenyl phosphite added as an antioxidant was 0.65 wt% of the amount of MA-LLA oligomer used, the reactive extrusion temperature at which the twin-screw extruder performs reactive kneading and extrudes to granulate was 185°C, and the residence time of the material in the twin-screw extruder was 15 minutes. Here, the infrared spectra of L-lactide, maleic anhydride, and maleic anhydride-grafted lactide are shown in Fig. 1a, b, and c, respectively. The infrared difference spectra of PLA, maleic anhydride, maleic anhydride-grafted polylactic acid (MAH-g-PLA), and maleic anhydride-grafted polylactic acid (MAH-g-PLA) and polylactic acid after subtraction of their spectra are shown in Fig. 2a, b, c, and d, respectively. 13 The CNMR spectra of polylactic acid and maleic anhydride-grafted polylactic acid are shown in Figure 3a and b, respectively. 13 The C NMR spectra are shown in Figures 4a and 4b, respectively. As can be seen from FIG. 1, in the infrared spectrum of maleic anhydride grafted lactide, -1 The out-of-plane bending vibration peak of the olefinic hydrogen of =CH appears at 1600 cm-1 The stretching vibration peak of -C=C- appeared, which indicated that maleic anhydride was successfully grafted onto lactide. As can be seen from FIG. 2, in the infrared difference spectra of MAH-g-PLA and pure PLA, -1 The absorption peak of the C=O group appears at 1190 cm -1 , 1130cm -1 and 1093 cm -1 The absorption peaks of COC appear in the infrared spectrum of MAH-g-PLA compared with that of PLA, and the absorption peaks of carbonyl and ether bonds are enhanced in the infrared spectrum of MAH-g-PLA, which indicated that MAH was successfully grafted onto the PLA polymer chains. Comparing Figure 3 a and b, the peaks of two types of carbon atoms in the anhydride group increased at chemical shifts of 70 ppm and 18 ppm, indicating that maleic anhydride was successfully grafted to L-lactide. Comparing Figure 4 a and b, there was a peak of the carbon atom of the anhydride group at a chemical shift of 169 ppm, and a peak of the carbon atom after the carbon-carbon double bond of maleic anhydride was cleaved at a chemical shift of 72 ppm, which indicated that MAH was successfully grafted onto the PLA polymer chain. The presence of terminal hydroxyl groups was determined by chemical titration. Examples 2 to 11

[0070] The reaction conditions, material types, and amounts of materials added were specifically shown in Table 1, but the polylactic acid graft copolymer was prepared according to the same steps and methods as in Example 1. Example 12

[0071] A polylactic acid graft copolymer was prepared by the method of Example 1, except that the nucleophilic addition reaction conditions were a temperature of 170° C. and a reaction pressure of 5 kPa. Example 13

[0072] A polylactic acid graft copolymer was prepared by the method of Example 1, except that the amount of maleic anhydride added was 310 wt % of the amount of L-lactide used, and the amount of dicumyl peroxide added was 6 wt % of the amount of L-lactide used. Example 14

[0073] A polylactic acid graft copolymer was prepared by the method of Example 1, except that the amount of stannous octanoate added as a catalyst in the ring-opening polymerization reaction was 5 wt % of the amount of the nucleophilic addition product used, and the amount of triphenylphosphine added as an initiator was 5 wt % of the amount of the nucleophilic addition product used. Example 15

[0074] The polylactic acid graft copolymer was prepared according to the method of Example 1, except that the amount of antioxidant added in the chain extension reaction was 5 wt% of the amount of the ring-opening polymerization product used, and the temperature of the ring-opening polymerization reaction was 250°C. Example 16

[0075] A polylactic acid graft copolymer was prepared by the method of Example 1, except that maleic anhydride was replaced with methyl methacrylate. Example 17

[0076] A polylactic acid graft copolymer was prepared by the method of Example 1, except that L-lactide in the nucleophilic addition reaction was changed to D-lactide. Comparative Example 1

[0077] As in the prior art, polylactic acid graft copolymers were prepared by a method in which L-lactide was polymerized and then grafted. (1) L-lactide (LLA) was subjected to low-temperature prepolymerization under nitrogen flow and negative pressure conditions by the action of a catalyst and an initiator to obtain an LLA oligomer. The low-temperature prepolymerization was carried out at a reaction temperature of 130°C, a reaction time of 3h, a reaction pressure of 300kPa, a flow rate of the nitrogen flow of 3m / s, and based on the weight of L-lactide (LLA), the amount of stannous octanoate added as a catalyst was 0.5wt% of the amount of LLA used, and the amount of triphenylphosphine added as an initiator was 0.2wt% of the amount of LLA used. (2) The LLA oligomer prepared in step (1) was added to a twin-screw extruder to undergo a polymerization reaction, and maleic anhydride (MA) and an antioxidant were added, followed by high-temperature reactive kneading, extrusion and granulation, and finally a maleic anhydride-grafted polylactic acid material (MA-PLLA) was obtained. Based on the weight of the LLA oligomer, the amount of maleic anhydride added was 2.5 wt% of the amount of the LLA oligomer used, and the amount of triphenyl phosphite added as an antioxidant was 0.5 wt% of the amount of the LLA oligomer used, and the extrusion temperature of the reaction in which reactive kneading was performed using a twin-screw extruder and extrusion and granulation were performed was 180°C. The presence of terminal hydroxyl groups is not determined by chemical titration. Comparative Example 2

[0078] The polymer was prepared according to the method disclosed in Example 1 of CN 104371082 A. Into a high-pressure reactor, add 30g lactide, 3g maleic anhydride, 9mg stannous octanoate, 3mg benzoyl peroxide and 50ml toluene, introduce nitrogen for 5 minutes to remove oxygen gas, react under sealed conditions at 200℃ for 20h, then cool with water, open the reactor, pour the solution into a portion of anhydrous methanol, stir to remove unreacted material, then suction filter, and vacuum dry the powder obtained by suction filter to obtain a non-discolored polylactic acid modified with maleic anhydride. The presence of terminal hydroxyl groups was determined by chemical titration. Comparative Example 3

[0079] The polymer was prepared according to the method disclosed in Example 1 of CN 104371082 A, except that the amount of maleic anhydride added was 140 wt% of the amount of L-lactide used. The presence of terminal hydroxyl groups was determined by chemical titration.

[0080] [Table 1] JPEG2025502485000010.jpg228169

[0081] [Table 2]

[0082] From Table 2, it can be seen that by using the method disclosed in the present invention, the grafting reaction of the graft group is carried out before the polymerization of lactide, the grafting efficiency is greatly improved, and the toughness, breaking elongation and glass transition temperature of the polylactic acid material are improved, and the prepared graft-modified polylactic acid copolymer material is environmentally friendly and completely biodegradable.

[0083] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, a number of simple modifications can be made to the technical solution of the present invention, including combining each technical feature in another suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed in the present invention, and all fall within the protection scope of the present invention.

Claims

1. Contains a repeating structural unit of the structure represented by formula (A), A polylactic acid graft copolymer characterized in that it has a right-angle tear strength of 120 kN / m or more, preferably 135 to 150 kN / m, and a breaking elongation of 30% or more, preferably 35 to 45%. 【Chemistry 1】 (Here, R 1 is H or a graft group, and the R 1 At least a portion of the is a graft group.

2. The content of the graft group is 1 2. The polylactic acid graft copolymer according to claim 1, wherein the content of said polylactic acid graft copolymer is 10 mol % or more, preferably 30 mol % or more, and more preferably 40 mol % or more of the total amount of said polylactic acid graft copolymer.

3. The polylactic acid graft copolymer according to claim 1 or 2, wherein the graft group has a structure represented by formula (I) and / or formula (II). 【Chemistry 2】 (Here, R 1 , R 2 , R 3 , R 4 , and R 5 are each independently hydrogen or a C1-C4 substituted or unsubstituted alkyl; R 6 is a C1-C6 substituted or unsubstituted alkyl, or a C6-C20 aryl.

4. 13 The polylactic acid graft copolymer according to any one of claims 1 to 3, which has a peak at a chemical shift of about 169 ppm and a peak at a chemical shift of about 72 ppm in CNMR.

5. The weight average molecular weight is 1×10 5 ~4×10 5 The polylactic acid graft copolymer according to any one of claims 1 to 4,

6. The polylactic acid graft copolymer according to any one of claims 1 to 5, which has a glass transition temperature of 80 to 100°C.

7. The polylactic acid graft copolymer according to any one of claims 1 to 6, which contains a terminal hydroxyl group as determined by a phthalic anhydride method.

8. (1) contacting lactide with a monomer having formula (i) and / or formula (ii) under nucleophilic addition reaction conditions to obtain a nucleophilic addition product; Step (2) of mixing the nucleophilic addition product obtained in step (1) with a catalyst and an initiator under ring-opening polymerization reaction conditions to perform low-temperature prepolymerization to obtain a ring-opening polymerization product; and step (3) polymerizing the ring-opening polymerization product obtained in step (2) at high temperature in the presence of an antioxidant under chain extension reaction conditions. 【Chemistry 3】 (Here, R 1 ', R 2 ', R 3 ', R 4 ', and R 5 Each ' is independently hydrogen or a substituted or unsubstituted C1-C4 alkyl; R 6 ' is a C1-C6 substituted or unsubstituted alkyl, or a C6-C20 aryl.

9. In the step (1), the nucleophilic addition reaction is carried out in the presence of an initiator, The preparation method according to claim 8, wherein the initiator is preferably dicumyl peroxide and / or 2,5-dimethyl-2,5-bis-(t-butylperoxy)hexane.

10. The preparation method according to claim 9, wherein the amount of the initiator added is 0.1-5 wt%, preferably 0.5-2 wt%, of the amount of the lactide used.

11. The preparation method according to any one of claims 8 to 10, wherein the conditions of the nucleophilic addition reaction include a reaction temperature of 50 to 150°C, a reaction pressure of 2 to 100 kPa, and a reaction time of 0.5 to 10 h.

12. The preparation method according to any one of claims 8 to 11, wherein the total amount of the monomers represented by the formula (i) and the formula (ii) added is 100 to 300 wt%, preferably 150 to 200 wt%, of the amount of the lactide used.

13. The method further comprises the step of removing the lactide not involved in the nucleophilic addition reaction by vacuum distillation after the step (1), and subjecting the resulting product to the reaction in step (2); The preparation method according to any one of claims 8 to 12, wherein the conditions of the reduced pressure distillation include a temperature of 100 to 200°C, a pressure of 0 to 100 kPa, and a time of 1 to 10 h.

14. In the step (2), the catalyst is at least one selected from stannous octanoate, zinc lactate, trialkylaluminum, triisobutylaluminum, and stannous chloride; Preferably, the amount of catalyst added is 0.1-5 wt %, preferably 0.5-2 wt %, of the total weight of the nucleophilic product; and / or the initiator is at least one selected from glycerol, xylitol, ethylene glycol, and triphenylphosphine; The preparation method according to any one of claims 8 to 13, wherein the amount of initiator added is preferably 0.05-5 wt %, preferably 0.3-2 wt % of the total weight of the nucleophilic product.

15. The preparation method according to any one of claims 8 to 14, wherein the conditions of the ring-opening polymerization reaction in step (2) include a reaction temperature of 100 to 150°C, a reaction pressure of 100 to 1000kPa, and a reaction time of 2 to 15h.

16. In the step (3), the antioxidant is at least one selected from phosphites, alkyl polyphenols, and thiobisphenol antioxidants; The preparation method according to any one of claims 8 to 15, wherein the amount of added antioxidant is preferably 0.1-5 wt%, preferably 0.5-2 wt% of the total weight of the ring-opening polymerization product.

17. The process according to any one of claims 8 to 16, wherein in step (3), the temperature of the chain extension reaction is 140-250°C, preferably 160-200°C.

18. The process according to any one of claims 8 to 17, wherein step (3) is carried out in a twin screw extruder.

19. A polylactic acid graft copolymer prepared by the method according to any one of claims 8 to 18.

20. Use of the polylactic acid graft copolymer according to any one of claims 1 to 7 and 19 in the preparation of agricultural mulch films, food packaging materials, and medical and sanitary products.

Citation Information

Patent Citations

  • Technology for preparing high-molecular-weight MPLGA by directly grafting maleic anhydride onto PLGA

    CN105315412A

  • Composite resin composition

    JP1999124485A

  • Method for grafting functional groups onto synthetic polymers to produce biodegradable plastics

    JP1999511804A

  • Modified polyester

    JP2007254714A

  • LA polymer composition

    JP2015529722A